2019
DOI: 10.3233/jad-190908
|View full text |Cite
|
Sign up to set email alerts
|

Flotillin is a Novel Diagnostic Blood Marker of Alzheimer’s Disease

Abstract: Currently, best-characterized indicators for Alzheimer's disease (AD) diagnosis are the decreased levels of amyloid-␤ protein 42 and increased levels of phosphorylated tau in cerebrospinal fluid (CSF). The positron emission tomography (PET) imaging with Pittsburgh compound B (PiB) is also used in AD diagnosis by visualizing amyloid deposition in the brain. These methods are invasive or expensive; therefore, less invasive and easily detectable blood biomarkers are required. Because our previous study showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Proteomic analyses have already indicated that flotillins are constituents of CSF-derived exosomes [58,59]. Importantly, flotillin levels can be relatively easily measured by ELISA method and/or immunoblot analysis [10], providing a significant advantage compared with other biomarker candidates that may require more expensive and specialized equipment.…”
Section: Flotillin As a Novel Biomarker Candidate For Ad: Clinical Evmentioning
confidence: 99%
See 4 more Smart Citations
“…Proteomic analyses have already indicated that flotillins are constituents of CSF-derived exosomes [58,59]. Importantly, flotillin levels can be relatively easily measured by ELISA method and/or immunoblot analysis [10], providing a significant advantage compared with other biomarker candidates that may require more expensive and specialized equipment.…”
Section: Flotillin As a Novel Biomarker Candidate For Ad: Clinical Evmentioning
confidence: 99%
“…Interestingly, a recent clinical study has indicated that flotillin levels were lower not only in the CSF, but also in the serum of AD patients, compared with subjects with mild cognitive impairment (MCI) or age-matched non-AD controls [10]. Additionally, CSF and serum flotillin levels have been shown to be reduced in patients with AD-related MCI, compared with non-AD-related MCI (determined by PiB-PET) [10].…”
Section: Flotillin As a Novel Biomarker Candidate For Ad: Clinical Evmentioning
confidence: 99%
See 3 more Smart Citations